E-Learning Research Trends in Higher Education in Light of COVID-19: A Bibliometric Analysis - Brika, Said Khalfa Mokhtar; Chergui, Khalil; Algamdi, Abdelmageed; Musa, Adam Ahmed; Zouaghi, Rabia (Frontiers in Psychology, 2022)
The paper reviews the origins of e-learning as a concept that has been widely used in the academic and professional communities and approved an educational approach considering COVID-19. The article starts with the literature review of e-learning. Diverse subjects have appeared on e-learning, which indicates the fields dynamic, various, and multidisciplinary aspects. Analysis of the most influential authors and analyses of models and networks for bibliometric analysis, and progress to the current research of the most critical areas. A bibliometric review analyses the data of 616 studies published (2020-2021) in the Web of Science database (ISI) to fully understand this field. The data was examined using VOSviewer and KnowledgeMatrix Plus to extract networks and bibliometric indicators about keywords, authors, organisations, and countries. The study concluded with several results in higher education. Many converging words or sub-fields of e-learning in higher education include distance learning, distance learning, interactive learning, online learning, virtual learning, computer-based learning, digital learning, and Blended learning. Hybrid learning. Research is currently mainly focused on pedagogical techniques, particularly e-learning and collaborative learning, but these are not the only trends developing in this area. The sub-field of Artificial Intelligence, Machine Learning and Deep Learning constitutes a new research direction for e-learning in light of COVID-19 and suggests new approaches for further analysis.